SPE/DOE Improved Oil Recovery Symposium 1996
DOI: 10.2118/35461-ms
|View full text |Cite
|
Sign up to set email alerts
|

Plugging of High Permeability - Fractured Zones Using Emulsions

Abstract: Low crude oil sweep efficiency may be the result of channeling of injected water through high permeability sands in heterogeneous reservoirs. In these cases the efforts have been focused in improving the distribution of injected water in the wellbore through treatments using cements, gelling agents, and other short radius plugging materials. It has been proven that such treatments contribute to a better water distribution in the formation around the wellbore However, they are unlikely to be completely successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…From a practical point of view, this high‐apparent viscosity at this low velocity can be unfavorable because it can damage the injectivity. This may result in low injection rates for a certain drawdown pressure . In general, all molar compositional fractions of miscible CO 2 ‐C 10 mixture exhibit shear‐thinning behavior, because the apparent viscosity decreases by increasing the velocity.…”
Section: Resultsmentioning
confidence: 99%
“…From a practical point of view, this high‐apparent viscosity at this low velocity can be unfavorable because it can damage the injectivity. This may result in low injection rates for a certain drawdown pressure . In general, all molar compositional fractions of miscible CO 2 ‐C 10 mixture exhibit shear‐thinning behavior, because the apparent viscosity decreases by increasing the velocity.…”
Section: Resultsmentioning
confidence: 99%
“…Romero et al studied on the effect of fracture plugging of in situ O/W emulsions by injection of an optimum amount of water/oil ratio in sandpacks and observed a massive reduction of 90% in water relative permeability as well as injectivity. This matter even was more evident in the initial part of their model (Romero et al 1996). According to Starvland et al (2006), the amount of this permeability reduction varies from zone to zones, with regard to the fluids saturations.…”
Section: Introductionmentioning
confidence: 88%
“…They created an emulsion with a high percentage of water content and introduced it in one of the oil reservoirs in the North Sea to diminish water cut up to 30% in their oilfield study (Bai et al 2000). Furthermore, the other advantages of O/W of emulsion flooding are its accessibility and lower cost of transportation as well as its more in-depth coverage into the formation and so its undemanding injectivity (Hasan et al 2010;Kumar and Mahto 2016;Mcauliffe 1973a, b;Romero et al 1996;Yu et al 2018). Romero et al studied on the effect of fracture plugging of in situ O/W emulsions by injection of an optimum amount of water/oil ratio in sandpacks and observed a massive reduction of 90% in water relative permeability as well as injectivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the conditions lead to improved sweep efficiency after water flooding. Previous studies have shown that emulsions could be used to increase water viscosity, decreasing mobility ratios resulting in a more efficient oil recovery [10][11][12][13][14][15]. Recent studies on the recovery of heavy oils by emulsion flooding have shown good potential for this recovery process in conjunction with water flooding [16][17][18].…”
Section: Introductionmentioning
confidence: 99%